2010
DOI: 10.1177/1077546309349850
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and Controlling Chaos in a Permanent Magnet Synchronous Motor

Abstract: In most situations, the high performance of permanent magnet synchronous motors (PMSMs) depends on an absence of chaos; consequently, suppressing chaos becomes quite important. Therefore, this study confirms the chaotic motion and then applies synchronization to a chaotic PMSM system to control chaos. Rich dynamics of the PMSM system are studied using a bifurcation diagram, phase portraits, a Poincaré map, frequency spectra and Lyapunov exponents. First, the largest Lyapunov exponent is estimated using synchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The bifurcation and chaos phenomenon of system (4) are studied in the literatures [12][13][14][15][16][17][18][19][20][21][22][23]. It has been found that the PMSM experiences chaotic behavior when the initial conditions of system states and the operating parameters σ and γ fall in a certain area.…”
Section: Chaotic Model Of Pmsmmentioning
confidence: 99%
See 1 more Smart Citation
“…The bifurcation and chaos phenomenon of system (4) are studied in the literatures [12][13][14][15][16][17][18][19][20][21][22][23]. It has been found that the PMSM experiences chaotic behavior when the initial conditions of system states and the operating parameters σ and γ fall in a certain area.…”
Section: Chaotic Model Of Pmsmmentioning
confidence: 99%
“…Zhang and Ding [16] proposed an adaptive control to achieve the chaos synchronization in two PMSMs. The Lyapunov exponent control for the chaos in PMSM was investigated in [17][18][19]. However, the parametric uncertainties and external disturbances, which are usually encountered in practical situations, are not taken into account in most research works shown above.…”
Section: Introductionmentioning
confidence: 97%
“…Its application to secure communications was computationally demonstrated. Chang (2010) confirmed chaotic motion in a permanent magnet synchronous motor (PMSM) and applied synchronization to a chaotic PMSM system to control its chaos. A proposed continuous feedback control method based on synchronization characteristics could eliminate chaotic oscillations.…”
Section: Introductionmentioning
confidence: 96%
“…The occurrence of chaos in motor drive systems was introduced by Kuroe and Hayashi [12] in the late of 1980 and since then, scientists and researchers have worked on different methods to identify, suppress and synchronize the chaos phenomenon in motor drives [3], [13], [2], [5], [11], [7].…”
Section: Introductionmentioning
confidence: 99%